2022
DOI: 10.33448/rsd-v11i2.25831
|View full text |Cite
|
Sign up to set email alerts
|

Pathogenicity of Beauveria bassiana to Atta sexdens rubropilosa (Hymenoptera: Formicidae) in laboratory conditions

Abstract: This research, under laboratory condition, evaluated the efficiency of different strains of entomopatogenic fungus Beauveria bassiana to control leaf-cutting ant Atta sexdens rubropilosa. Soldiers and workers were inoculated with suspensions containing 1.0x107, 1.0x108, 1.0x109 and 1.0x1010 con mL-1 and maintained in B.O.D, at 25±1°C, 70% RH and 12 hours of photophase, without food. The mortality was evaluated daily, with 15 days after inoculation. Experimental design was entirely random. The sporulation data … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 6 publications
0
4
0
Order By: Relevance
“…The research occurred in both: 1. laboratory: bait preparation and evaluation of bait quality; 2. field: evaluation of bait acceptance and carrying of different concentration of fungi conidia incorporated in the baits. So, this research can be qualified as qualitative and quantitative (see Alves 1988;Loureiro et al 2022aLoureiro et al , 2022b.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The research occurred in both: 1. laboratory: bait preparation and evaluation of bait quality; 2. field: evaluation of bait acceptance and carrying of different concentration of fungi conidia incorporated in the baits. So, this research can be qualified as qualitative and quantitative (see Alves 1988;Loureiro et al 2022aLoureiro et al , 2022b.…”
Section: Methodsmentioning
confidence: 99%
“…The prospecting for non-polluting methods aimed at managing populations of leaf-cutter ant species, which have pest status in agrosilvipastoral systems is of paramount importance. Techniques that use physical barriers to protect trees and shrubs, have shown to be more promising (Jiménez et al, 2022), as well as the population suppression methods with biological weapons, especially entomopathogenic fungi (Loureiro et al, 2022a(Loureiro et al, , 2022b. The coexistence with leaf-cutting ant species should be sought, in order to enable the production of food free of pesticides; without major damage to rural producers, avoiding the local extinction of Attini species, because that last mission, is a task that is not only ecologically undesirable, but also, probably, impossible.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…One biological agent that shows toxicity to ants is the Beauveria bassiana fungus, which is commercially available and widely used in agriculture and forestry (Li et al 2011). It has been extensively studied, showing prospects for future success in ant management (Cantú-Ruiz et al 2017;Folgarait et al 2020;Loureiro et al 2022). The success of using B. bassiana may be true because it has been observed that there are isolates of B. bassiana that cause mortality of 87% of A. sexdens workers after 4 days of application (Loureiro et al 2005).…”
Section: Introductionmentioning
confidence: 99%